Highly selective-notch band ultrawide band antenna: A review - Anees Abbas; Wahaj Abbas Awan; Niamat Hussain; Domin Choi; Sangmin Lee; Nam Kim (Heliyon)
Ultra-wideband (UWB) technology offers a unique alternative for communicating over short distances due to its high capacity and low power consumption during transmission and reception. However, designing an antenna with appropriate characteristics for these systems is a significant problem since it must avoid interfering with current limited bandwidth technologies (e.g., Wi-Fi, lower 5G, and satellite downlink band) in the UWB range. In this review article, we have made a comprehensive literature review of quasi-perfect-notch band UWB antennas that have been reported with different techniques used. The ever-growing demand for antennas in wireless communications has challenged researchers to design antennas with innovations for highly efficient communications between end users. Adding external filters has the disadvantage of large volume and high cost. To overcome these problems the researchers have proposed different band-notch techniques to mitigate the interferences in this densely populated wireless network era. The primary objective of this review article is to offer comprehensive insights into various highly selective notch-band UWB antennas, presenting a clearer overview of the techniques used to mitigate interference from narrowband signals that overlap with the UWB spectrum. The methods used—which include applying EBG structures, incorporating SRRs, slot etching, and using stubs—are covered in detail in different sections.